Pengaruh Kompetensi Guru dan Implementasi Kurikulum Asing Terhadap Kinerja Guru di Sekolah Internasional Jakarta Utara - Domina Elfrida (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
This study aims to investigate the influence of teachers’ competence and implementation of international curriculum on teachers’ performance in North Jakarta International Schools. This research was conducted based on the problem that there were still many teachers who do not have good performance. This research uses quantitative study with a survey and interviews to collect data from the respondents. This study employs path analysis technique to test the hypothesis. The sample in this study is 55 teachers in North Jakarta International Schools which is taken by using simple random sampling. The results show that (1) teachers’ competence has a positive and effect on teachers’ performance, (2) the implementation of international curriculum has a positive effect on teachers’ performance, and (3) teachers’ competence has a positive effect on the implementation of international curriculum.